Bendrinės lietuvių kalbos intervokalinių priebalsių kiekybė (spektrografinis tyrinėjimas) - Tankevičiūtė, Marytė (Kalbotyra, 1981)
To establish the intrinsic duration of Lithuanian consonants, 4,921 “Visible Speech” type spectrograms and approximately as many oscillograms were made. The experiment was carried out at the Experimental Phonetics Laboratory of Vilnius University.The data obtained by spectrographical analysis were estimated statistically and, if necessary, verified by the so-called student’s criterion. The analysis has given the following results: Lithuanian consonants of all modal types have their intrinsic duration. It is determined to a high degree by the manner of articulation and the voicing of a consonant. Another differential feature – velarization vs. palatalization of a consonant – is not relevant for the duration of Lithuanian consonants. The duration is strongly affected by the length of a phrase; both the position of the logical stress and local features of articulation have no effect on their duration.